Sejarah Perkembangan Ushul Fiqih, Tokoh-Tokoh Ushuliyah, dan Kitab-Kitab Ushul Fiqih - Siti Rahmaayu Dwi Permatasari; Riska Amalia Ramadani; Muhammad Imam Sejati; Kurniati Kurniati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This abstract discusses the history of the development of ushul which includes the role of influential figures and books in the discipline. The history of the development of ushul fiqh began from the beginning of the Islamic era to the modern era. This article aims to discuss the figures of ushuliyyah who have a role in compiling books that are the basis for understanding the principles of ushul fiqh. The research methodology used in reviewing this article is descriptive qualitative. This article also uses a library research approach, and data collection carried out in this article is carried out by reviewing or searching for sources from several journals, books, and research that has been done (both printed and electronic). Based on the results of the data analysis, it is known that the main figures of ushuliyyah have produced ushul fiqh books such as As-Syafi'i with the book "Al-Umm" Malik bin Anas with the book "Al-Muwatta", and Al-Sarakhsi with the book "Al-Mabsut" which is a general basis for understanding Islamic law. The development of ushul fiqh is also influenced by the thoughts and contributions of other figures whose works remain an important foundation in the study of ushul fiqh to this day.